Aestuarium zhoushanense is a later heterotypic synonym of Marivivens donghaensis, and transfer of Paradonghicola geojensis to the genus Marivivens as Marivivens geojensis comb. nov. Issue 11 (11th November 2022) - Qu, Luxuan; Li, Yating; Wang, Wanpeng; Shao, Zongze; Gao, Zheng; Lai, Qiliang
Abstract : The 16S rRNA genes of Aestuarium zhoushanense G7 T and Paradonghicola geojensis FJ12 T shared 100 % sequence identity with Marivivens donghaensis AM-4 T . Phylogeny of 16S rRNA gene sequences showed that the three type strains formed a monophyletic clade within the genus Marivivens . Whole genome sequence comparisons showed that three type strains shared 46.7–69.7 % digital DNA–DNA hybridization, 92.1–96.4 % average nucleotide identity and 96.2–98.1 % average amino acid identity. The high 16S rRNA gene similarity values show that three type strains should belong to the same genus. The pan-genome of the five strains contained 5754 genes including 1877 core genes. Based on the principle of priority, we propose that A. zhoushanense Yu et al . 2019 is a later heterotypic synonym of M. donghaensis Park et al . 2016, and P. geojensis should be reclassified as Marivivens geojensis comb. nov., respectively.